Local Wisdom and Career Meaning-Making among Final-Year University Students: An Ethnographic Study of Minangkabau Culture - Masril Masril; Rahmat Hidayat; Louis Downs (Yayasan Keluarga Guru Mandiri, 2026)
Career development is often conceptualized as an individual and rational process; however, in culturally embedded societies, it is profoundly shaped by local values, social norms, and collective identities. This study aims to explore how local wisdom influences career meaning-making among final-year university students within the Minangkabau socio-cultural context of Tanah Datar, West Sumatra. This study employed a qualitative ethnographic design involving 21 participants: 15 final-year students from diverse academic disciplines and 6 key informants, including lecturers, career practitioners, and community leaders. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using thematic analysis through systematic coding and categorization. The findings reveal that career development is constructed as a culturally embedded process characterized by five key themes: collective responsibility, value-based filtering through local wisdom, merantau as a culturally embedded career pathway, negotiation between tradition and modernity, and cultural identity as the foundation of career orientation. Career decisions are strongly influenced by family expectations, moral values, and social recognition, while local wisdom functions as both a symbolic and evaluative framework guiding career choices. This study contributes to the development of culturally grounded career theory by emphasizing the importance of integrating local wisdom and socio-cultural contexts into career guidance practices in higher education.